A Comparative Study between Radiocephalic and Brachiocephalic Arteriovenous Fistula in End Stage Renal Disease - Sabah, Md Nazmus; Ahmed, SM Parvez; Khan, Md Saif Ullah; Hasan, Rakibul; Hossain, Md Fidah; Fatma, Manifa Naz (Cardiovascular Journal, 2021)
Background: Chronic Kidney Disease (CKD) is a major health issue all over the world. Patients with deteriorating renal function and end-stage renal disease require vascular access for hemodialysis. Studies suggest that Arterio-Venous fistula (AVF) constructed judiciously using autologous conduit give the best outcome in this regard. Objective of the study was to compare the outcomes of Radiocephalic and Brachiocephalic AVF in end stage renal disease (ESRD). Methods: It was a quasi-experimental study carried out at the Department of Vascular Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. The study was conducted from June 2019 to May 2020. Patients suffering from ESRD underwent AVF creation surgery for hemodialysis access. A total of 60 (Sixty) patients were included in this study. The patients were divided into two groups; Group I included 30 patients who underwent Radiocephalic AVF operation and Group II included 30 patients who had Brachiocephalic AVF operation. Results: In Group I, (Radiocephalic AVF) 60% were male and 40% were female. On the other hand, in Group II (Brachiocephalic AVF) 73.3% were male and 26.7% were female. Calculated volume flow (Q max) was significantly higher in Group II compared with Group I (769.11±101.54 ml/min vs 626.37±55.81) ml/min) with the difference being statistically significant (P=0.001). Maturation time was significantly less in Group II compared with Group I )37.78±1.93 vs 43.33±2.12 days) with the difference between the two group being statistically significant (P=0.001). Complication was more in Group I than Group II (16.7% vs 3.3%). Conclusion: The present study shows that Brachiocephalic AVF gives significantly better outcome in terms of shorter maturation time and less complications compared with Radio-Cephalic AVF. Color Doppler study is an essential tool for preoperative vessel evaluation which guides the selection of suitable AVF construction site. Cardiovasc j 2021; 14(1): 44-49